Preface (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2020)
This special issue is a collection of selected papers in physics presented in the International Conference on Advances in Communication Technology, Computing and Engineering (ICACTCE'21), to be organized by High School of Technology, Moulay Ismail University Meknes, Morocco and Faculty of Sciences and Techniques Mohammedia, Hassan II University, Morocco from 24 to 26 March, 2021 (virtually from Morocco). The scope of this conference is to provide a platform for researchers, engineers, academicians as well as industrial professionals from all over the world to present their research results and development activities in various topics of Engineering and Technology. It allows participants an opportunity to discuss the recent developments in the field of solidification computer science and engineering and review challenges faced by the community in the 21st century. Due to COVID-19, this edition of conference is fully online and the participation is totally Free of Charge.EditorsMariyam OuaissaHigh School of TechnologyMoulay Ismail University MeknesMoroccoMariya OuaissaHigh School of TechnologyMoulay Ismail University MeknesMoroccoSarah El HimerFaculty of Sciences and TechnologiesSMBA University FezMoroccoZakaria BoulouardFaculty of Sciences and Techniques MohammediaHassan II UniversityMorocco